The Crossroad of Technology: Does IBW Develops The Creativity Of Elementary School Students? - Pečiuliauskienė, Palmira; Saylik, Agnė (Pedagogika, 2013)
The article discusses the possibilities of the development of creative writing skills of primary school pupils while using interactive whiteboard. Creative writing skills are described with respect to the features of creative thinking: anticipation of the title of narrative corresponding to the essence of the story (originality); disclosure of the topic of narrative according to the number of statements described (elaboration); logic and sequence of narrative (flexibility); structure of narrative and anticipation of its main parts (fluency). The problem of the research is to determine how application of interactive whiteboard in educational practice effects creative writing skills of primary school pupils. The object of the research is the development of creative writing skills of primary school pupils while using interactive whiteboard. The research aims at evaluating the influence of the use of interactive whiteboard as an additional learning tool to the improvement of creative writing skills of primary school pupils. The study conducted by authors during Lithuanian language lessons in primary grades showed that interactive whiteboard can have a positive effect on pupils’ creative writing skills if it is used as addition rather than an alternative tool. This was ensured by authors’ chosen methods of teaching narrative writing: interactive whiteboard was used as a traditional board during the first three lessons while the forth lesson was dedicated to interactive teaching with the full use of interactive whiteboard and its possibilities. Results show that educational effectiveness of interactive whiteboard to pupils’ creative writing skills depends on the appropriate use of its complex components in educational practice.